Pelaksanaan Kewenangan Direktur Jenderal Pajak Untuk Mengurangi Atau Membatalkan Sengketa Pajak - Alexander Candra; Djafar Albram; Hasbi Hasan (Postgraduate of Jayabaya University, 2019)
Taxation Laws Rules and regulations are still under supervision by the Ministry of Justice and Human Rights with the operational implementation by the Director General of Taxation in terms of both formal and material law. For the oversee this acceptance, it is necessary to peratuan tax legislation is clear, unequivocal and there is no overlapping, so wajip taxes or taxpayers can more obedient, and a sense of justice has high accountability. It may indirectly increase state revenue and the authority to enforce the law. The research method used by the authors in the discussion of this research, is the normative research methods, which outlines what the applicable tax law is in conformity with the norms of other formal legal. According to the Tax Act No. 28 of 2007, Article 36 of the Director General of Taxes may also decide to reduce, correct, cancel or eliminate penalties and interest and administration of tax assessment issued. As for the decision process of determining the tax to be paid, so the moot court in the Director General of Taxes. Courts are decided in accordance with the Tax Court Act No. 14 of 2002, is the principal authority under the power of the judiciary, can run with the principles of the judicial process, which is low cost, fast and fair. With the recent reform Tax Courts embrace principles Cheap, Fast, Simple and Fair.